Counter‐Accounting with Invisible Data: The Struggle for Transparency in Myanmar's Energy Sector. Issue 1 (May 2014) - MacLean, Ken
<x xml:space="preserve">Abstract</x> This article examines the counter‐accounting methods one NGO, EarthRights International (ERI), uses to make Myanmar's notoriously opaque energy sector more transparent. ERI's methodological approach relies heavily on the identification of "invisible data, " which do not appear in the statistics that governments and foreign energy companies release concerning their joint ventures. However, the data leave patterned traces in other statistical financial data. ERI asserts that it is possible to reconstruct joint venture balance sheets by comparing these traces against what the principles have not disclosed, such as with the controversial Yadana pipeline and the precedent‐setting human rights lawsuit connected to it. The choices that ERI made illustrate how financial "facts" are fashioned rather than found, and that technical decisions regarding who does the counting, what gets counted, and what is disclosed to whom are profoundly political in nature. Such decisions also foreground key limitations of NGO‐led revenue transparency projects, especially in resource‐rich countries. Greater data disclosure does not necessarily result in increased transparency. Rather, the proliferation of structured and unstructured data sources (information that is organized and readily searchable versus information that is not) often leads to greater disagreement among key stakeholders regarding the relevance, neutrality, intelligibility, and verifiability of the numbers available for audit.